AT-THIBAQ DALAM AL-QURAN SURAT AL-BAQARAH – AT-TAUBAH (TINJAUAN BALAGHAH) (Universitas Negeri Semarang, 2018)
In the Quran surat Al-Baqarah up At Sura found the opposite meaning words in one sentence or in sciencebalaghah called ath-thibaq, that is the style of the language between the two opposites in a phrase. If the twoopposites are not different from the positive and negative thibaq it is called a consent, while in the opposite thetwo words it is called a thibaq salab. The problem in this study is 1) anything containing the words of ath-thibaqin the Quran surat Al-Baqarah At-Tawba, up 2) How these kinds of ath-thibaq in the Quran surat Al-Baqarahup At Sura and 3) How the shape of the ath-thibaq in The Quran surat Al-Baqarah until At-Tawba. This typeof research is qualitative research design the research library research. The data of this research in the form of aword that contains a ath-thibaq. Data source derived from the Quran surat Al-Baqarah until At-Tawba. Thisresearch data gathering techniques using the techniques of documentation with the card data as an instrument.The data in this study are presented using the technique of sampling considerations (purposive sampling). Theresults of this study researchers found 438 data ath-thibaq in the Al-Quran, i.e. 350 data thibaq consent and 88salab thibaq data. From a total of 438 data ath-thibaq found in the Quran, researchers just choose 90 thibaq athdatato be analyzed to the maximum. From the data analyzed indicate 90 60 30 thibaq data consent and datathibaq salab. Of the 60 data thibaq consent consists of 24 data thibaq consent isim with isim, 23 data thibaqconsent fi'il with fi'il, 1 data thibaq consent charf with charf and 12 data thibaq consent from two different types(isim and fi'il). As for the 30 data thibaq salab comprising 2 thibaq salab isim with isim, 25 thibaq salab fi'ildata with fi'il and 3 thibaq salab data from two different types (isim and fi'il). Dalam Al-Quran surat Al-Baqarah sampai At-Taubah banyak ditemukan lafal yang berlawananmaknanya dalam satu kalimat atau dalam ilmu balaghah disebut dengan ath-thibaq, yaitu gaya bahasayang memadukan antara dua kata yang berlawanan dalam sebuah ungkapan. Jika dua kata yangberlawanan tersebut tidak berbeda positif dan negatifnya maka disebut thibaq ijab, sedangkan apabiladua kata yang berlawanan tersebut berbeda positif dan negatifnya maka disebut thibaq salab. Duakata yang berlawanan tersebut bisa terdiri dari isim dengan isim, fi’il dengan fi’il, charf dengan charfatau dari dua jenis yang berbeda (isim dan fi’il). Jenis penelitian ini adalah penelitian kualitatif dengandesain penelitian library research. Data penelitian ini berupa kata yang mengandung ath-thibaq.Sumber datanya berasal dari Al-Quran surat Al-Baqarah sampai At-Taubah. Teknik pengumpulandata penelitian ini menggunakan teknik dokumentasi dengan kartu data sebagai instrumennya. Datadalam penelitian ini disajikan dengan menggunakan teknik sampel pertimbangan (purposivesampling). Hasil penelitian ini peneliti menemukan 438 data ath-thibaq dalam Al-Quran surat Al-Baqarah sampai At-Taubah, yaitu 350 data thibaq ijab dan 88 data thibaq salab. Dari total 438 dataath-thibaq yang ditemukan dalam Al-Quran surat Al-Baqarah – At-Taubah, peneliti hanya memilih90 data ath-thibaq untuk dianalisis secara maksimal. Dari 90 data yang teranalisis menunjukkan 60data thibaq ijab dan 30 data thibaq salab. Dari 60 data thibaq ijab terdiri atas 24 data thibaq ijab isimdengan isim, 23 data thibaq ijab fi’il dengan fi’il, 1 data thibaq ijab charf dengan charf dan 12 data thibaqijab dari dua jenis yang berbeda (isim dan fi’il). Adapun 30 data thibaq salab yang terdiri atas 2 thibaqsalab isim dengan isim, 25 data thibaq salab fi’il dengan fi’il dan 3 data thibaq salab dari dua jenis yangberbeda (isim dan fi’il).